The Academic Assistance and its Relationship with the College and Stage Variables at the Department of Kindergarten’s Students: نبأ مجيد مطشر, و جميلة رحيم عبد (Journal of the College of Education for Women, 2021)
The study aims at knowing students’ academic assistance at the Department of Kindergarten. It further aims to know the difference of academic assistance among these students with respects to variables like (college of education for women, Baghdad, Thi-Qar). It also aims to know about the difference according to the academic level variable, in addition to its relation to some other variables. To achieve the objectives of the study, a number of university female students were selected from both Baghdad an Thi-Qar Universities in the academic year 2019-2020. The sample of the participants consisted of (400) students from the (second, third, and fourth) levels. To measure the study variable represented by the concept of academic assistance, the researchers designed a measurement test following the scientific steps followed when preparing psychological measurements. Then, the validity and reliability of the measuring test was derived. The researchers further used statistical tools to derive the findings of the study, such as Pearson’s factor, the t-test, and variance analysis). The study has concluded that students have the ability to ask for academic assistance. Besides, there are statistical differences of the academic assistance according to the college variable. Moreover, there are differences of academic assistance between the second and fourth levels in favor of the second level, and between the third and fourth in favor of the third.